Workshop dan Pelatihan Pembelajaran Berbasis Higher Order Thinking Skill (HOTS) - Budyartati, Sri; Jamilah, Jamilah; Khalik, Suhartini; Rahayu, Arum Putri; Kosilah, Kosilah (Carmin: Journal of Community Service, 2024)
Madiun is a city in East Java Province, Indonesia. The fourth largest city in East Java, after Surabaya, Malang, and Kediri, is 160 km west of Surabaya, or 111 km east of Surakarta, Central Java. The fourth largest city in East Java after Surabaya, Malang and Kediri. This city has a railroad industry (INKA) and a railroad high school. Based on the data above, the social capital owned by the city of Madiun must be maintained and increased from time to time as the times change and progress. Therefore, society and the world. Education in Madiun must keep up with the times by updating or reforming, learning innovations to be at the forefront, and at least not to be left behind. Higher-order thinking, known as higher-order thinking skills (HOTS), is an educational reform concept based on learning taxonomies (such as Bloom's taxonomy). The idea is that some types of learning require more cognitive processing than others but have more general benefits. The problem is that the busyness of teachers and the community and the lack of time to think about and carry out updates make teachers less active in implementing innovations or reforms in education. To overcome this problem, it is necessary to provide education and training on various ways of updating learning. The implementation method is carried out through lectures, demonstrations, and workshops to school inspectors and school principals in Madiun. Evaluation of the pretest results regarding the HOTS workshop showed that understanding increased by 19% with indicators during the activity, 90% of the participants were enthusiastic about practicing it, and 100% had made updates by carrying out HOTS-based learning. This community service is one of the PGRI Madiun University programs that implement the Tri Dharma of Higher Education by conducting training on implementing HOTS-based learning.